An octavalent dendrimer of multiple antigenic peptide with a property of pan-coronavirus IgM induction improved clinical signs of feline infectious peritonitis in cats - Nara, Takuya; Shimoda, Hiroshi; Suzuki, Chitose; Tran, Ngo Thuy Bao; Tsukada, Hina; Okayama, Hiroki; Weiyin, Hu; Obata, Miho; Mitsunaga, Saki; Sakurai, Masashi; Kuroda, Yudai; Maeda, Ken; et al. (Veterinary vaccine, 2024)
Feline infectious peritonitis (FIP) is a lethal disease caused by a pathogenic coronavirus, feline infectious peritonitis virus (FIPV), in cats. Effective vaccines have been unsuccessful due to the frequent mutation of FIPV and antibody-dependent enhancement (ADE) caused by vaccine-induced IgG antibodies (Abs). This study examined the induction of pan-coronavirus IgM Ab in mice and its ameliorating effects in feline FIP using CoV-mMAP8, an octavalent dendrimer composed of multiple antigenic peptides. The 11-amino acid peptide (SAIEDLLFNKV) was designed as the highly conserved region of the fusion peptide at the N-terminus of S2’ subunit of the spike protein found in human and animal coronaviruses and was then conjugated to an octavalent dendrimer to form CoV-mMAP8. After a total of three injections of CoV-mMAP8 into Balb/c mice with α-galactosylceramide (α-GC) co-administered in the second injection, serum titers of IgM Abs increased against the peptide, recombinant spike proteins of SARS-CoV-2 and MERS-CoV, and crude viral antigens of canine coronavirus, porcine endemic diarrhea virus, and FIPV. In contrast, serum titers of IgG Abs did not significantly increase against any antigens. When CoV-mMAP8 was injected into three cats experimentally infected with FIPV, hyperthermia was improved within seven days after the injection with ameliorating inflammatory markers such as the platelet-to-lymphocyte ratio and the systemic immune-inflammatory index. One cat that showed recurrent hyperthermia received an additional injection of CoV-mMAP8, and clinical improvement was observed again. Postmortem examinations confirmed chronic lesions of FIP in all the cats, providing evidence that FIPV had been successfully infected and treated with CoV-mMAP8 in all the cats. Based on the induction of pan-coronavirus IgM Abs in mice and ameliorating effects in FIP of cats, it is assumed that CoV-mMAP8 has the potential to overcome the challenges posed by variants and ADE in FIPV. The mutational compatibility of CoV-mMAP8 can make it a viable universal vaccine for various coronaviruses beyond FIPV.